Psychometric Properties of a Measure of Borderline Personality Organization in a Spanish Court-Referred Partner-Violent Male Sample - Redondo Rodríguez, Natalia; Gómez, José Luis Graña; Montesino, María Luisa Cuenca; Muñoz-Rivas, Marina Julia (Frontiers in Psychology, 2019)
Borderline Personality Organization (BPO) is a key personality component of partner-violent men. The study described in this paper examines the psychometric properties of the Borderline Personality Organization Scale (BPO Scale; Oldham et al., 1985) in a Spanish sample of 643 men undergoing court-mandated psychological treatment after conviction for episodes of intimate-partner violence. Three confirmatory factor analyses were carried out first, and the three-factor structure of the BPO scale was then tested. Results for concurrent validity show positive and significant correlations between the subscales and the overall BPO scale, and with other instruments that measure borderline and antisocial personality, and impulsivity. The BPO scale also presents evidence of known-groups validity, since BPO scores decrease with age, and of discriminant validity, as the scale discriminates between participants who do and do not exceed the cutoff point on a borderline personality scale. The Borderline Personality Organization Scale is a suitable instrument for evaluating BPO in partner-violent men.